The efficacy and safety of anticoagulation for the management of gonadal vein thrombosis: A systematic review and pooled analysis - Sara Ng; Cameron Brown; Farah Zarka; Aurélien Delluc; Marc Carrier (Thrombosis Update, 2024)
Background: Gonadal vein thrombosis (GVT) is an uncommon condition that has been associated with different risk factors (e.g., post-partum period, cancer, recent pelvic surgery, etc.). The optimal management of GVT remains unclear. We sought to assess the efficacy and safety of anticoagulation therapy in adult patients with GVT. Methods: A systematic search of MEDLINE, EMBASE and PubMed, from inception to February 2023 was performed. The primary efficacy outcome was recurrent venous thromboembolism (VTE). Bleeding outcomes were assessed in the form of major and clinically relevant non-major bleeding (CRNMB) events. Incidence rates of the outcomes were pooled using the random effects model and expressed as event per 100 patient-years with its associated 95 % confidence intervals (CI) using R software. Results: A total of 14 observational studies and one randomized controlled trial (1134 patients) with GVT met the inclusion criteria and were included in the review. Overall, 429 (37.8 %) patients were treated with anticoagulation. The rate of recurrent VTE was 3.1 per 100 patient-years (95 % CI, 1.6–6.3). The rate of major bleeding and CRNMB events were 1.0 (95 % CI; 0.2–4.5) and 9.9 (95 % CI; 2.6–37.8) per 100 patient-years, respectively. Conclusion: Gonadal vein thrombosis seems to be associated with a relatively low risk of recurrent VTE and bleeding complications. The risk benefit ratio of anticoagulant therapy remains unclear in this patient population.